RESEPSI ESTETIS: SENI BACA AL-QUR’AN DALAM ACARA PERNIKAHAN - Silfi Mahfudhiyah; Adrika Fithrotul Aini (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2020)
The tradition of wedding receptions created a new tradition in the art of reading the Qur'an. The Qur'an is recited at weddings with different rhythms. This difference is important to study. The purpose of the study was to determine the type of rhythm of the song recited by the qori at the wedding, the correlation between the theme of the wedding, the meaning of the verses of the Qur'an, and the rhythm of the recitation, as well as the response of the reciter and mustamik in the event. This research is qualitative research using field research for two months. The theory of ethnomusicology becomes a reference for the answers to the existing questions. The rhythm of the song at the wedding: ijᾱz, Rast, Sikᾱ,Nahᾱwand, Bayyᾱtī with various variations. The theme of the wedding ceremony focuses on verses that are following the meaning of the verses of the Qur'an about marriage, and the meaning of the verses of the Qur'an affect the reciter in reciting the verses of the Qur'an. The reception of the reciter is taḥadduṡ bi al-ni'mah through tawassul to the recitation teacher in the hope of obtaining blessings in reading the Qur'an. The mustamik reception of the reciter in marriage are different, listening and perceiving the meaning; listening to the rhythm and imitating readings; indifferent.